Intelligence Cooperation Practices in the 21st Century: Towards a Culture of Sharing - Tuzuner, Musa (IOS Press, 2013)
Security cooperation, be it intranational, bilateral, or transnational, evolves around the basic idea of some kind of sharing. Information naturally grows when it is shared, not only as an accumulation of separate parts, but as an evolving, organic body of knowledge that in turn sparks further knowledge. Based on this premise, a group of leading practitioners and scholars in the field of intelligence were brought together to discuss the modern dynamics of intelligence sharing. This edited volume presents a selection of their contributions and provides an original and practice-driven analysis of the challenges for current security and intelligence cooperation. Intelligence Cooperation Practices in the 21st Century: Towards a Culture of Sharing will be of interest to students, scholars and practitioners of international relations, intelligence, terrorism, security and policing. “Security scholarship has long suffered from a gap that exists between scholars and practitioners. This gap leads to unfortunate discrepancies, both at the conceptual and practical levels. Dr. Tuzuner’s edited volume is one of the rare attempts to bridge this divide in a particularly sensitive area of security studies. The various contributions are full of original insights, which are sure to inspire invaluable further research and inquiry.” Ersel Aydinli, Bilkent University, Turkey